Escaping the 'Field Trap': exploitation and the global politics of educational fieldwork in 'conflict zones' - Mitchell, Audra (Third world quarterly, 2013)
There is a growing global demand for Northern universities to provide fieldwork opportunities in 'conflict zones' to students in applied International Relations (peace and conflict studies, post-conflict studies, human rights, development and related fields). This demand is generated in macro-level or structural dynamics emerging from three sources: the hiring criteria of major international organisations, competition between universities for fee-paying students and the social commodification of 'authentic' or 'real' life experience. At the micro level these dynamics can manifest themselves in exploitative relations, two of which are explored here. First, substantial inequalities (or a 'benefit gap') may arise between student researchers and their research subjects. Second, student researchers may find themselves in extractive relations with their research subjects. These dynamics lead to a situation in which some of the world's most vulnerable people are objectified as learning resources for students enrolled in (predominantly Northern) universities. The article argues that these dynamics are a problem of global politics, not just research ethics or pedagogy. It concludes with recommendations for reducing the potential for exploitation in educational fieldwork.